How to create an ORKG Comparison - An example from Computer Science - Oelen, Allard (Technische Informationsbibliothek (TIB), 2022)
ORKG Comparisons present an overview of the state-of-the-art for specific research questions. Learn how to create a comparison with this example in the domain of computer science.
Keywords: Information Science; ORKG; Open Research Knowledge Graph; Comparison